Low-mass Eclipsing Binaries KIC 4908495, KIC 6466939, and KIC 9474485: Isolated Pre-main-sequence Systems? - Orkun Özdarcan (The Astrophysical Journal, 2025)
We present a detailed analysis of three Kepler eclipsing binaries, KIC 4908495, KIC 6466939, and KIC 9474485. Our analysis reveals that these systems are composed of components possessing a lower mass than our Sun with slight subsolar metallicities. Individual analysis of the evolutionary status of each system interestingly suggests that all component stars in all three systems are pre-main-sequence (PMS) stars that have already developed a radiative core and are on the way to the zero-age main sequence in the Hertzsprung–Russell diagram. Estimated ages are 25 ± 5, 22 ± 6 and 25 ± 15 Myr for KIC 4908495, KIC 6466939 and KIC 9474485, respectively. However, none of these systems is a cluster or association member, indicating that the targets might be isolated eclipsing binaries possessing PMS components. Kepler light curves show noticeable wave-like variability at out-of-eclipse parts, suggesting a considerable magnetic activity manifesting as the rotational modulation of cool surface spots or spot groups. Projected rotational velocities of the components and amplitude spectrum of out-of-eclipse variability suggest either asynchronous rotation of the component stars or the surface differential rotation of the magnetically active component.